Re-assessment of E-S-Qual scale in the internet banking services in Turkey - Teuman, Abdullah Behçet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Service quality and the effective measurement of service quality on the Internet has been drawing much attraction lately with the increasing use of the World Wide Web. Researchers and managers focus on the construction of scales to measure electronic service quality, which assess customer satisfaction and loyalty as an ultimate goal. E-S-Qual is the most recently developed and popular e-service quality measurement technique on which there are quite a number of testing efforts. In this study, the E-S-Qual scale is re-assessed for Internet banking services in Turkey. The original E-S-Qual model has been adapted for Internet banking and the questionnaire has been developed accordingly. The reliability and factorial validity of adapted E-S-Qual model has been tested with the data of 382 observations. Confirmatory Factor Analysis has been conducted on the adapted E-S-Qual model and the model has been re-specified for a reliable, valid and conceptually sounding construct. After the evaluation of the findings following the successive testing of the re-specified E-S-Qual model, it is concluded that the refined scale is effective in Internet banking services in Turkey. Electronic Service Recovery Quality (E-RecS-Qual) is not included in this study because there are not enough observations to analyze.
Keywords: Internet banking -- Turkey -- Case studies.; Customer services -- Evaluation.